Modern Passings Death Rites, Politics, and Social Change in Imperial Japan - Bernstein, Andrew (University of Hawaii Press, 2006)
These include a government wanting to separate itself from religion even while propagating State Shinto, the appearance of a new middle class, and new forms of transportation.As these and other developments created new contexts for old rituals, Japanese faced the problem of how to fit them all together. What to do with the dead? is thus a question tied to a still broader one that haunts all societies experiencing rapid change: What to do with the past? Modern Passings is an impressive and far-reaching exploration of Japan’s efforts to solve this puzzle, one that is at the heart of the modern experience
Description based on online resource; title from PDF title page (publisher's Web site, viewed 21. Nov 2017)
Keywords: Geschichte 1868-2000; Totenkult; Sozioökonomischer Wandel; Japan